2022
DOI: 10.1136/bjsports-2021-105118
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of exercise via telehealth for chronic disease: a systematic review and meta-analysis of exercise interventions delivered via videoconferencing

Abstract: ObjectiveTo investigate the effectiveness of videoconferencing exercise interventions for people with chronic diseases.DesignSystematic review incorporating meta-analysis.Data sourcesPubMed, Cinahl, MEDLINE, Web of Science, Embase and Scopus.Eligibility criteriaThe current literature was searched following Preferred Reporting Items for Systematic Reviews and Meta-Analysis guidelines. Trials analysing participants with chronic disease undergoing aerobic and/or resistance exercise training over videoconferencing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 90 publications
0
24
1
Order By: Relevance
“…This may be particularly important for high priority groups including indigent, rural, and remotely located and indigenous peoples where cost and access can be key barriers to exercise adoption and maintenance. Strategies to promote affordable access to exercise support could include telehealth, mHealth or eHealth technologies [42][43][44][45] as well as group-based exercise session to reduce individual cost and/ or providing hospital community health infrastructure.…”
Section: Discussionmentioning
confidence: 99%
“…This may be particularly important for high priority groups including indigent, rural, and remotely located and indigenous peoples where cost and access can be key barriers to exercise adoption and maintenance. Strategies to promote affordable access to exercise support could include telehealth, mHealth or eHealth technologies [42][43][44][45] as well as group-based exercise session to reduce individual cost and/ or providing hospital community health infrastructure.…”
Section: Discussionmentioning
confidence: 99%
“…To improve patient safety, adverse events and/or patient safety events should be consistently reported. However, reviews of in-person rehabilitation studies show that adverse events are often underreported and/or inconsistent,41,42 and this trend seems to hold true for telehealth rehabilitation studies with as low as 9% of studies in a systematic review reporting on adverse events 43,44. Such inconsistent reporting of adverse events prohibits positive growth for improving patient safety, which not only is integral to the mission of health care systems but also is a critical component of health care professionals' competencies.…”
Section: Discussionmentioning
confidence: 99%
“…Previous literature has suggested that the implementation of exercise-based telehealth technologies can be safe, effective and feasible for patients among various chronic disease cohorts. [25][26][27] Additionally, there is good evidence to suggest that telehealth lifestyle interventions are cost-effective when compared to usual care. 28 With these results in mind, it should be recognised that AEPs have a role to play in both the uptake and promotion of telehealth modalities for all patients.…”
Section: Discussionmentioning
confidence: 99%